An Empirical Investigation of Virtual Networking Sites Discontinuance Intention: Stimuli Organism Response-Based Implication of User Negative Disconfirmation - Ma, Weigang; Tariq, Anum; Ali, Muhammad Wasim; Nawaz, Muhammad Asim; Wang, Xingqi (Frontiers in Psychology, 2022)
The study's prime objective is to investigate the user discontinuance intention in the shed of the negative disconfirmation of user expectation. The study has derived the theoretical structure from the expectancy disconfirmation theory (EDT) enacted through the stimuli organism response (SOR) framework to study the actual cause and effect relationship of human behavioral response. To investigate the user discontinuance intention behavioral response, a total of 434 correct and complete answers were shortlisted for analysis. To examine the data set, the study has used the modern partial least square method technique or simply SmartPLS service package to run the structural equation modeling (SEM). Moreover, the study has implied the 80/20 rule run the mediating analysis of the SOR framework. The statistical results show that all three stimuli make significant positive disconfirmation of the user beliefs in terms of dissatisfaction and the anxiety that ultimately leads to the discontinuance intention in the virtual network users. Further, these results are validated through the six mediating relationships, which partially mediate the relationship between the stimuli and response. Besides all these findings, this study has made some practical and realistic theoretical and practical implications for both researchers and service-providing managers.